Diseño de protocolo para la conversión de vehículo con motor de combustión interna a motor eléctrico. (2022)
Electric vehicles are increasingly crucial in the energy transition in the transport sector and the reduction of pollutants. This project shows the transformation process from a conventional vehicle with an internal combustion engine to one with an electric motor. The objective is to incentivize the insertion of electric vehicles in Duitama city's taxi fleet.